2019
DOI: 10.1371/journal.pone.0213598
|View full text |Cite
|
Sign up to set email alerts
|

Functional interaction of human Ssu72 with RNA polymerase II complexes

Abstract: Phosphorylation of the C-terminal domain (CTD) of the large subunit of human RNA polymerase II (Pol II) is regulated during the transcription cycle by the combined action of specific kinases and phosphatases. Pol II enters into the preinitiation complex (PIC) unphosphorylated, but is quickly phosphorylated by Cdk7 during initiation. How phosphatases alter the pattern and extent of CTD phosphorylation at this early stage of transcription is not clear. We previously demonstrated the functional association of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Some of the top ten identified genes could be related to stress response, mainly Txnip, Angplt4, and Gstm7, but also S100a6 through inhibition of the interaction between heat shock proteins and Sgt1 or Hop . On the other hand, the highest ranked gene from the list, SSu72, plays a role in RNA processing and termination and could be related to the increase in transcription . To confirm and better understand the link between these genes and cold response in CHO cells would require further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the top ten identified genes could be related to stress response, mainly Txnip, Angplt4, and Gstm7, but also S100a6 through inhibition of the interaction between heat shock proteins and Sgt1 or Hop . On the other hand, the highest ranked gene from the list, SSu72, plays a role in RNA processing and termination and could be related to the increase in transcription . To confirm and better understand the link between these genes and cold response in CHO cells would require further studies.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37]39] On the other hand, the highest ranked gene from the list, SSu72, plays a role in RNA processing and termination and could be related to the increase in transcription. [33] To confirm and better understand the link between these genes and cold response in CHO cells would require further studies.…”
Section: Discussionmentioning
confidence: 99%
“…In MeCP2 ChIP-Seq in MDA-MB-468 cells, we found that MeCP2 binds to multiple novel targets not previously associated with MeCP2 function in the context of breast cancer. Some of these included the following genes: a) SSU72 Homolog, RNA Polymerase II CTD Phosphatase (SSU72), a protein phosphatase that catalyzes the dephosphorylation of the C-terminal domain of RNA polymerase II ( 66 ); b) CAPN2 (Calpain 2), a calcium-sensitive cysteine protease ( 67 ); c) Plexin B2 (PLXNB2), a class B transmembrane receptor that participates in axon guidance and cell migration in response to semaphorins ( 68 ); d) Zinc Finger SWIM-Type Containing 4 (ZSWIM4); e) RUNX Family Transcription Factor 3 (RUNX3) a transcription factor that functions as a tumor suppressor and is frequently deleted or transcriptionally silenced in cancer ( 69 , 70 ), and f) Solute Carrier Family 45 Member 4 (SLC45A4) ( Figure 1B ). Additionally, in MCF7 some of the notable genes included a) Ubiquitin Specific Peptidase 34 (USP34), a ubiquitin hydrolase that removes conjugated ubiquitin from AXIN1 and AXIN2, acting as a regulator of Wnt signaling pathway ( 71 ); b) Maltase–Glucoamylase (MGAM), an enzyme that plays a role in the digestion of starch ( 72 ); c) GDP-Mannose 4,6-Dehydratase (GMDS), an enzyme that participates in the synthesis of GDP-fucose from GDP-mannose ( 73 ); d) Solute Carrier Family 45 Member 4 (SLC45A4); e) CCDC26 Long Non-Coding RNA (CCDC26), a lncRNA class associated with Malignant Glioma and Astrocytoma ( 74 , 75 ); and f) Sidekick Cell Adhesion Molecule 1 (SDK1) ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of the genetic and physical interactions of Ssu72 with the promoter-bound factors implicated the protein in the assembly of the preinitiation complex (PIC) ( Ganem et al, 2003 ; Spector et al, 2019 ). Prior to initiation of transcription, the preinitiation complex (PIC) recruits RNAPII with a hypo-phosphorylated CTD.…”
Section: Biological Functionsmentioning
confidence: 99%